2000
DOI: 10.1046/j.1365-2168.2000.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy, peptic ulcer disease and the risk of adenocarcinoma of the oesophagus and gastric cardia

Abstract: Cholecystectomy, despite its effect on the composition of gastric juice, does not appear to increase the risk of adenocarcinoma of the oesophagus or gastric cardia. While the data do not contradict a protective effect of H. pylori, the results are also consistent with absence of such an effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 33 publications
(15 reference statements)
3
22
0
1
Order By: Relevance
“…Two case control studies [20,21] with 321 cases between them and one cohort study [22] based on 91 cases, found that cholecystectomy, despite its effect on gastric juice did not appear to increase the risk of oesophageal adenocarcinoma. By contrast, two cohort studies [23,24] based on 179 cases, found a moderate association between cholecystectomy and subsequent oesophageal adenocarcinoma, however, the absolute risk was found to be small.…”
Section: Oesophageal Adenocarcinoma and Squamous Cell Carcinomamentioning
confidence: 96%
See 2 more Smart Citations
“…Two case control studies [20,21] with 321 cases between them and one cohort study [22] based on 91 cases, found that cholecystectomy, despite its effect on gastric juice did not appear to increase the risk of oesophageal adenocarcinoma. By contrast, two cohort studies [23,24] based on 179 cases, found a moderate association between cholecystectomy and subsequent oesophageal adenocarcinoma, however, the absolute risk was found to be small.…”
Section: Oesophageal Adenocarcinoma and Squamous Cell Carcinomamentioning
confidence: 96%
“…Two case control [20,21] and one cohort study [28] based on a total of 478 cases found that prior cholecystectomy was not associated with an increased risk of gastric cardia cancer. The results from a meta-analysis [25] which included two studies specific for gastric cardia cancer [20,28] found that cholecystectomy was not associated with risk of gastric cardia cancer(SRRs = 0.87, 95%CI: 0. 65-1.17).…”
Section: Gastric Cancermentioning
confidence: 96%
See 1 more Smart Citation
“…Data were derived from the population-based Eindhoven Cancer Registry, which covers approximately two million inhabitants in the southeast of The Netherlands [5]. They are served by 16 community hospitals and two large radiotherapy institutes that collaborate with the Cancer Registry within the framework of the Comprehensive Cancer Centre South, IKZ.…”
Section: Study Populationmentioning
confidence: 99%
“…gastro-oesophageal junction (GOJ)] adenocarcinomas in The Netherlands has been increasing during past decades, especially in males [1][2][3][4][5]. Causal factors underlying the upward trend in incidence in GOJ adenocarcinomas are not yet elucidated.…”
Section: Introductionmentioning
confidence: 97%